Analisis Peranan Koperasi Simpan Pinjam Dalam Upaya Pengembangan UMKM Pada KSP Makmur Mandiri - Adzra Ghina Nazifah; Laras Fiela Indraningrum; Lusti Kristina Ayu Saputri Manalu; Novi Purnamasari; Rheisyah Indah Cahyani (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the role of the Makmur Mandiri Savings and Loan Cooperative (KSP) in supporting the development of Micro, Small, and Medium Enterprises (MSMEs). KSP Makmur Mandiri serves as a microfinance institution providing financial access and business mentoring for MSME actors. The method used is qualitative descriptive with a Group Investigation approach, involving group discussions to gain deeper insights from relevant literature sources such as journals and books. The theoretical review supports understanding the cooperative’s role in improving member welfare and the obstacles faced in managing and developing MSMEs. The findings show that KSP Makmur Mandiri has succeeded in providing continuous capital and support, helping MSMEs to survive and grow despite economic challenges, especially after the pandemic. However, the cooperative faces various internal and external obstacles that require strategic collaboration for sustainable development. The implication of this study is to encourage enhanced managerial capacity of cooperatives and the need for stronger government policy support to optimize the cooperative’s role as a strategic partner for MSMEs.